New records of predaceous midges from the Middle East, with the description of two new species (Diptera: Ceratopogonidae) - Dominiak, Patrycja; Alwin, Alicja; Giłka, Wojciech (Zootaxa, 2013)
Two new distinctive species of predaceous biting midges of the tribe Ceratopogonini are described and illustrated from the Middle East. Brachypogon freidbergi sp. nov., with a unique Y-shaped gonostylus, is recorded from Israel. We also provide the first records of Brachypogon vitiosus (Winnertz) and B. aethiopicus (Clastrier, Rioux & Descous) from this country, and a key to the adult males of the genus Brachypogon Kieffer from the Middle East. Ceratopogon azari sp. nov., described from Lebanon, shows a distinctive structure of the male genital apparatus, and is the southernmost species of that genus in the Western Palaearctic.